Systematic Literature Review: Analysis of Misconception Problems and Diagnostic Instruments for Learning Chemistry - Muhammad Habib Ash Shiddiqi; Vegha Dwi Arthamena; Mizzan Ayyubi; Alessandro Jeremi Manarisip; Nurfina Aznam (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to analyze research trends in Chemical misconceptions in chemistry learning and diagnostic instruments used. The research method used in this research is a systematic literature review (SLR). The database obtained was 16 articles selected from the Scopus and Google Scholar databases with Publish or Perish (PoP). The results of the research found were the majority of students experienced misconceptions in learning chemistry caused by errors in preconceptions and abstract thinking concepts in the material, the method used to analyze the misconceptions found was a two-level, three-level, four-level diagnostic instrument, multiple choice, and semi-open tests and The misconceptions found in chemistry materials are acid-base, reaction rate, chemical equilibrium, chemical bonding, salt hydrolysis, and buffer solution.